Enhancing nutrient intake, egg production, and egg quality by fermented Leucaena leucocephala leaf meal in a diet of laying quail - Merry Muspita Dyah Utami; Abigeil Akbar (Veterinary World)
Background and Aim: The inclusion of Leucaena leucocephala leaf meal (LLM) in poultry feed is often limited due to its high crude fiber and mimosine content. This study investigates the potential of fermented LLM (FLM) to enhance nutrient intake, egg production, and egg quality in laying quails by reducing anti-nutritional factors through fermentation.